Practice and associated factors determination of self-medication with antibiotics among community residents in Boyolali, Indonesia: A cross-sectional study - Karuniawati, Hidayah; Suryawati, Sri; Syed Azhar, Syed Sulaiman; Taufik, Taufik; Wan Ismahanisa, Ismail; Hossain, Md. Sanower (Open Science Publishers LLP Inc., 2023)
This study investigated the prevalence, practice, and factors associated with self-medication with antibiotics (SMA) in the general community in Boyolali, Indonesia. This cross-sectional study used a validated questionnaire with the cluster sampling method applied to select households. Data were analyzed using chi-square and multivariate logistic regression analysis. During the study, 961 respondents participated (46.9% male and 53.1% female). The prevalence of SMA was 16%. Amoxicillin (50.0%) and tetracycline (33%) were frequently used as antibiotics for self-medication. The reasons for SMA were mainly personal experience and not consulting with a doctor to save money. Most respondents reported that antibiotics could kill viruses (84.3%) and reduce fever (73.2%). They do not know that antibiotics must be bought in a pharmacy after being prescribed by a doctor (66.8%) and do not know how to use antibiotics correctly (63.5%). Age, marital status, employment status, knowledge of antibiotic access, and knowledge of antibiotics misuse effect were significantly associated with SMA (p < 0.05). This study determined 16% SMA, but the tolerance to SMA should be zero because any single percent of SMA could spread antibiotic resistance widely among the whole community. Therefore, educating and encouraging people to avoid SMA is recommended to prevent ABR development and spread among societies.